Farmer Satisfaction on Concentrate Feed Produced by Dairy Feed Mill Cooperative: A Case Study: Kepuasan Peternak pada Pakan Konsentrat yang Diproduksi oleh Pabrik Pakan Koperasi Sapi Perah - Norma Nuraina; Atikah Nur Hamidah; Despal Despal; Epi Taufik (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2020)
The aims of this study were to evaluate the quality of feedstuff as concentrate feed raw material, the quality of feed concentrate, and customer satisfaction toward concentrate quality produced by the cooperative. The parameters observed were nutrient contents (moisture, ash, crude protein, crude fat, and crude fibre) and physical quality (density, bulk density, and compacted bulk density). Farmer satisfaction was measured using customer satisfaction index (CSI) and gap analysis. The data obtained consisted of primary data (nutrient content of feedstuff and physical quality) and secondary data (nutrient content of concentrates) that were then analysed descriptively. Total respondents in the satisfaction analysis were 100 farmers. The results of this study indicated that feedstuff nutrient content varied, even though corn gluten feed (CGF) was in the range of Indonesian National Standards (SNI). The highest density and bulk density were limestone, and the highest compacted bulk density was salt, while the lowest physical quality was coffee chaff. Nutrient content of concentrate complied with SNI except for crude fat content. Meanwhile, the physical quality of the concentrate was still within the normal range. Farmer satisfaction was in the satisfied category with the highest gap values absence of foreign objects. Key words: concentrate feed, CSI, farmer satisfaction, feedstuff, quality